1998
DOI: 10.1007/s11746-998-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of arachidonic acid production by Mortierella alpina 1S‐4

Abstract: The effect of mineral addition on arachidonic acid (AA) production by Mortierella alpina 1S-4 was evaluated. At first, the addition of minerals such as sodium, potassium, calcium, and magnesium was examined in flask cultures, and then the addition of phosphorus with the optimal amounts of the minerals was investigated in a 10-L jar-fermenter. As a result, 1.5% soy flour medium with the addition of 0.3% KH 2 PO 4 , 0.1% Na 2 SO 4 , 0.05% CaCl 2 ·2H 2 O, and 0.05% MgCl 2 ·6H 2 O was found to enhance the AA yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The main product of the strain, AA, is synthesized through the n-6 pathway, which involves 12 and 6 desaturases, elongase (EL2), and 5 desaturase. Depending on the conditions, the total amount of AA varies between 3 and 20 g/L (30-70% of the total cellular fatty acids), with 70-90% of the AA produced being present as triacylglycerols (Higashiyama et al, 1998Shimizu et al, 2003b). Although fatty acid desaturase inhibitors, such as cyclopropene fatty acids, and microbial uptake of supplemented fatty acids from cultural media were reported (Aggelis, 2003;Aggelis et al, 1997;Moreton, 1985), cultivation of the Mortierella strain under certain conditions also leads to a variety of PUFAs being produced, for example: (a) lowering of the growth temperature (<20 • C) with simultaneous addition of ␣-linolenic acid (18:3n-3) to the medium results in the production of EPA (Shimizu et al, 1988(Shimizu et al, , 1989b; (b) the addition of 5 desaturase inhibitors such as sesamin (Shimizu et al, 1991a) to the growth medium causes an increase in DGLA (Shimizu et al, 1989a); (c) utilization of C15 and C17 n-alkanes by the strain yields PUFAs with odd numbers of carbons in their chains (total C17 and C19 fatty acids reached over 95% of the mycelial fatty acids (Shimizu et al, 1991c); (d) n-1 PUFAs (20:5n-1, 20:4n-1, 18:4n-1, etc.)…”
Section: Arachidonic Acid-producing M Alpinamentioning
confidence: 99%
“…The main product of the strain, AA, is synthesized through the n-6 pathway, which involves 12 and 6 desaturases, elongase (EL2), and 5 desaturase. Depending on the conditions, the total amount of AA varies between 3 and 20 g/L (30-70% of the total cellular fatty acids), with 70-90% of the AA produced being present as triacylglycerols (Higashiyama et al, 1998Shimizu et al, 2003b). Although fatty acid desaturase inhibitors, such as cyclopropene fatty acids, and microbial uptake of supplemented fatty acids from cultural media were reported (Aggelis, 2003;Aggelis et al, 1997;Moreton, 1985), cultivation of the Mortierella strain under certain conditions also leads to a variety of PUFAs being produced, for example: (a) lowering of the growth temperature (<20 • C) with simultaneous addition of ␣-linolenic acid (18:3n-3) to the medium results in the production of EPA (Shimizu et al, 1988(Shimizu et al, , 1989b; (b) the addition of 5 desaturase inhibitors such as sesamin (Shimizu et al, 1991a) to the growth medium causes an increase in DGLA (Shimizu et al, 1989a); (c) utilization of C15 and C17 n-alkanes by the strain yields PUFAs with odd numbers of carbons in their chains (total C17 and C19 fatty acids reached over 95% of the mycelial fatty acids (Shimizu et al, 1991c); (d) n-1 PUFAs (20:5n-1, 20:4n-1, 18:4n-1, etc.)…”
Section: Arachidonic Acid-producing M Alpinamentioning
confidence: 99%
“…Under the optimal aging conditions, ARA yield was increased from 10.02 g/l after 6.5 days fermentation in a 5 l scaled fermentor to 19.02 g/l after another 5.6 days aging, which was higher than the previously reported yields [25][26][27]. The relatively high ARA yield displays the potential of using the improved aging technology in developing bioprocess for commercial production of ARA.…”
Section: Discussionmentioning
confidence: 71%
“…Berkley (19) studied a medium, in which low Mg was desirable for arachidonic acid (AA) production; the effect of addition of phosphorous on AA production has been studied by some groups (20)(21)(22). K. Higashiyana et al (17) reported the effect of addition of minerals, such as Na, K, Ca and Mg on arachidonic acid (AA) production by Mortierella alpina IS-4. He observed that 1.5% soy flour medium with the addition of 0.3% KH 2 PO 4 , 0.1% Na 2 SO 4 , 0.05% CaCl 2 .…”
Section: Effect Of Mineral Addition On Lipidmentioning
confidence: 99%